Impact of supervised exercise training on systemic sclerosis with multiple organ involvement: a case report - Alhowikan, Abdulrahman Mohammed (Journal of the Pakistan Medical Association, 2022)
Supervised training exercises are the mainstay of pulmonary rehabilitation (PR) in patients with chronic lung diseases like interstitial lung disease (ILD). A 40 years old female patient with systemic sclerosis clinically presenting with usual interstitial pneumonia (UIP) and pulmonary hypertension underwent an eight-week supervised exercise training programme. Forced Vital Capacity (FVC) showed improvement from 48.7% to 54% of predicted baseline, while the initial six-minute walk test (MWT) distance also showed a considerable increase of 15.4% from the baseline after completion of the exercise training. A remarkable improvement was noticed in muscle strength for both the upper and the lower limbs. There was an increase of 79.4% right side handgrip, 25% left side handgrip, and 30.9% increase in lower limbs than baseline strength. The findings show that an exercise training programme under the supervision of trained and competent staff can benefit the improvement of lung function —Continue